Mobile Technology to Increase HIV/HCV Testing and Overdose Prevention/Response among People Who Inject Drugs - Aronson, Ian David; Bennett, Alexander; Marsch, Lisa A.; Bania, Theodore C. (Frontiers in Public Health, 2017)
Abstract The United States faces dramatically increasing rates of opioid overdose deaths, as well as persistent ongoing problems of undiagnosed HIV and HCV infection. These problems commonly occur together in substance using populations that have limited, if any, access to primary care and other routine health services. To collectively address all three issues we developed the Mobile Intervention Kit (MIK), a tablet computer-based intervention designed to provide overdose prevention and response training, and to facilitate HIV/HCV testing in community settings. Intervention content was produced in collaboration with experienced street outreach workers who appear onscreen in a series of educational videos. A preliminary pilot test of the MIK in a Bronx, NY street outreach syringe exchange program (SEP) found the MIK is feasible and highly acceptable to a population of people who inject drugs (PWID). Participants accepted HIV and HCV testing post-intervention, as well as naloxone training to reverse overdose events. Pre-post tests also showed significant increases in knowledge of overdose prevention, HIV testing procedures, and asymptomatic HCV infection. Future iterations of the MIK can be optimized for use in community as well as clinical settings nationwide, and perhaps globally, with a focus on underserved urban populations.